A new method for Phytophthora cactorum culturing using host plant materials to prepare agar medium - Shengping Zhang; Ying Cheng; Jiaqiang Zhao; Kuijing Liang; Yupeng Pu; Guoliang Xu; Zhaohui Yang (Scientific Reports)
Abstract Phytophthora cactorum (Oomycota: Peronosporaceae), the agent of apple phytophthora rot, is known to infect over 200 plant species. Traditionally, P. cactorum is cultured in the laboratory on V8 juice agar medium. However, the use of commonly adopted materials for culturing P. cactorum is costly. Theoretically, host plant materials can be utilized to develop alternative agar media for culturing plant pathogens. However, research on utilizing host plant materials to prepare agar media for culturing P. cactorum has been limited. In this study, we employed chamber assays to identify host plant species of P. cactorum through artificial inoculation. Some of the healthy host plants were then individually selected to prepare agar media for screening. Our results demonstrate that host-derived juices, such as those from celery stems or oakleaf goosefoot leaves, support stronger sporulation capacity and higher average growth rates compared to V8 medium, suggesting that host plant tissues can be effectively used to produce agar media for culturing P. cactorum.